Clinical Outcomes of Osteochondral Lesions of the Tibial Plafond Following Arthroscopic Microfracture. (September 2019) - Lee, Wonyong; Tran, Sterling; Cooper, Minton T.; Park, Joseph S.; Perumal, Venkat
Background: The purpose of this study was to evaluate the clinical outcomes and the level of sports activity following arthroscopic microfracture for osteochondral lesions of the tibial plafond. Methods: A retrospective review was conducted for patients who underwent arthroscopic microfracture surgery for osteochondral lesions of the tibial plafond from January 2014 to June 2017. For functional evaluation, the visual analog scale (VAS) pain score, Foot and Ankle Ability Measure (FAAM) score, and Short Form-12 (SF-12) general health questionnaire were used. We also investigated the level of sports activity before and after the surgery. Sixteen patients were included in this study, and the mean follow-up period was 29.8 months. Results: The mean VAS score improved from 8.3 (range, 6-10) preoperatively to 1.8 (range, 0-4) postoperatively. The mean FAAM score was improved from 57.6 (range, 6.0-88.9) for the activities of daily living subscale and 34.5 (range, 3.1-92.6) for the sports subscale to 84.3 (range, 46.4-100.0) and 65.2 (range, 23.3-55.1) for each subscale, respectively, at the final follow-up. There were also improvements in the SF-12 score, from 36.3 (range, 23.3-55.1) preoperatively to 46.0 (range, 18.9-56.6) postoperatively for the SF-12 PCS, and from 41.3 (range, 14.2-65.0) preoperatively to 52.6 (range, 32.8-60.8) postoperatively for the SF-12 MCS. All functional scores showed significant differences clinically and statistically at the final follow-up. The level of sports activity after the surgery was significantly lower than their level before the surgery ( P = .012). Conclusion: Arthroscopic microfracture provided satisfactory clinical outcomes for osteochondral lesions of the tibial plafond. Though all the patients in this study were able to return to sports activity after the surgery, the postoperative level of sports activity was significantly lower than their preoperative level. Level of Evidence: Level IV, retrospective case series.